Transparent Porous Conductive Substrates for Gas‐Phase Photoelectrochemical Hydrogen Production. Issue 9 (2nd January 2023) - Caretti, Marina; Mensi, Elizaveta; Kessler, Raluca‐Ana; Lazouni, Linda; Goldman, Benjamin; Carbone, Loï; Nussbaum, Simon; Wells, Rebekah A.; Johnson, Hannah; Rideau, Emeline; Yum, Jun‐ho; Sivula, Kevin
Abstract: Gas diffusion electrodes are essential components of common fuel and electrolysis cells but are typically made from graphitic carbon or metallic materials, which do not allow light transmittance and thus limit the development of gas‐phase based photoelectrochemical devices. Herein, the simple and scalable preparation of F‐doped SnO2 (FTO) coated SiO2 interconnected fiber felt substrates is reported. Using 2–5 µm diameter fibers at a loading of 4 mg cm −2, the resulting substrates have porosity of 90%, roughness factor of 15.8, and Young's Modulus of 0.2 GPa. A 100 nm conformal coating of FTO via atmospheric chemical vapor deposition gives sheet resistivity of 20 ± 3 Ω sq −1 and loss of incident light of 41% at illumination wavelength of 550 nm. The coating of various semiconductors on the substrates is established including Fe2 O3 (chemical bath deposition), CuSCN and Cu2 O (electrodeposition), and conjugated polymers (dip coating), and liquid‐phase photoelectrochemical performance commensurate with flat FTO substrates is confirmed. Finally, gas phase H2 production is demonstrated with a polymer semiconductor photocathode membrane assembly at 1‐Sun photocurrent density on the order of 1 mA cm −2 and Faradaic efficiency of 40%. Abstract : Transparent gas diffusion electrodes are developed via the F‐doped SnO2 coating of SiO2 fused fiber felts. These highly porous and conductive substrates are amenable to the disposition of various semiconductors and are employed herein to demonstrate photoelectrode membrane assemblies for solar‐driven H2 production in a gas‐phase flow cell.